Microbial activity in the marine deep biosphere: progress and prospects - Orcutt, Beth N.; LaRowe, Douglas E.; Biddle, Jennifer F.; Colwell, Frederick S.; Glazer, Brian T.; Reese, Brandi K.; Kirkpatrick, John B.; Lapham, Laura L.; Mills, Heath J.; Sylvan, Jason B.; Wankel, Scott D.; Wheat, C G. (Frontiers in Microbiology, 2013)
The vast marine deep biosphere consists of microbial habitats within sediment, pore waters, upper basaltic crust and the fluids that circulate throughout it. A wide range of temperature, pressure, pH, and electron donor and acceptor conditions exists – all of which can combine to affect carbon and nutrient cycling and result in gradients on spatial scales ranging from millimeters to kilometers. Diverse and mostly uncharacterized microorganisms live in these habitats, and potentially play a role in mediating global scale biogeochemical processes. Quantifying the rates at which microbial activity in the subsurface occurs is a challenging endeavor, yet developing an understanding of these rates is essential to determine the impact of subsurface life on Earth's global biogeochemical cycles, and for understanding how microorganisms in these "extreme" environments survive (or even thrive). Here, we synthesize recent advances and discoveries pertaining to microbial activity in the marine deep subsurface, and we highlight topics about which there is still little understanding and suggest potential paths forward to address them. This publication is the result of a workshop held in August 2012 by the NSF-funded Center for Dark Energy Biosphere Investigations (C-DEBI) "theme team" on microbial activity (www.darkenergybiosphere.org).